PERSEPSI UMKM DI KOTA PONTIANAK TERHADAP TAX AMNESTY - B41112066, RHESI ALHAMZA LUBIS (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
This study aims to find out the results of the perception and knowledge of SMEs in Pontianak about Tax Amnesty. The sample of this study are SMEs in Pontianak which amount 100. Perception and knowledge of Tax Amnesty measured by spreading the questionnaire. Analysis of data using descriptive method. The results of this study that the level of knowledge of SMEs in Pontianak about Tax Amnesty is good. This means that SMEs can understand intent and purpose of the enactment of Tax Amnesty itself. However, the level of knowledge is not directly proportional to the perception, which in this study obtained results on the perception of SMEs in Pontianak about Tax Amnesty is not good.Kata Kunci : Perception, SMEs, Tax Amnesty